2005
DOI: 10.1089/jmf.2005.8.545
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementation of Traditional Medicinal Plants on Blood Glucose in Non–Insulin-Dependent Diabetics: A Pilot Study

Abstract: The effect of supplementation of a powdered mixture of three traditional medicinal plants-bittergourd, jamun seeds, and fenugreek seeds-in raw and cooked form on blood glucose was studied in 60 non-insulin-dependent male diabetics. The patients were divided into two groups of 30 each. The patients of group I were given the raw powdered mixture in the form of capsules; the patients of group II were given this mixture in the form of salty biscuits. Daily supplementation of 1 g of this powered mixture for a 1.5-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…Several small preliminary clinical studies investigating the effect of seed extracts of Trigonella foenum-graecum revealed a significantly reduced insulin resistance [50] and improved fasting and postprandial blood glucose levels [51,52] in diabetic patients. Isolated compounds of fenugreek, when administered in addition to sulfonylureas, also showed an improved anti-diabetic action compared to sulfonylureas alone in diabetic patients [53].…”
Section: Discussionmentioning
confidence: 99%
“…Several small preliminary clinical studies investigating the effect of seed extracts of Trigonella foenum-graecum revealed a significantly reduced insulin resistance [50] and improved fasting and postprandial blood glucose levels [51,52] in diabetic patients. Isolated compounds of fenugreek, when administered in addition to sulfonylureas, also showed an improved anti-diabetic action compared to sulfonylureas alone in diabetic patients [53].…”
Section: Discussionmentioning
confidence: 99%
“…Various parts of the plant are used for treatment of a variety of human abnormalities. The seed is able to lower blood glucose rapidly and so is effective in treating diabetes [38,39] and hyperinsulinemia [40]. Seed extracts are rich in phenols and show high-antioxidant activity [41].…”
Section: Discussionmentioning
confidence: 99%
“…A combination regimen of bitter melon and fenugreek seeds was found to have a synergistic effect in lowering blood sugar levels. In a similar study, a powdered mixture of bitter melon fruit, jamun seeds, and fenugreek seeks administered to 60 non-insulin-dependent male diabetics significantly reduced their fasting and postprandial glucose levels and decreased their dose of oral hypoglycemic drugs [41]. …”
Section: Clinical Reportsmentioning
confidence: 99%